SANAsms: Secure short messaging system for secure GSM mobile communication - Anuar, N.B.; Azlan, I.M.; Wahid, A.W.A.; Zakaria, O. (2008)
SANAsms or Short Messaging System (SMS) Encryption System is as application on mobile phone that enables to send, receive and store encrypted text messages. Users are able to exchange sensitive messages using SMS because the message is in an encrypted and a protected form, which it is hard for the attacker or non-authorize person to read the messages. As a result, the system makes the confidential data in SMS text become safer and secure in such case of the device lost or stolen. SANAsms is capable to send confidential encrypted information in SMS via normal GSM and it only can be read by person who can decrypt it. Currently, normal SMS using GSM communication is not secured and safe enough. One of the solutions is to have a security application implemented in mobile phone device. Therefore, SANAsms system ensures that information (SMS) interchange between sender and receiver is secured and protected because the messages containing delicate information are stored securely and remain undisclosed even when the device is accessed by an adversary. The system is developed using Java 2 Micro Edition (J2ME) which is written in Java. J2ME phone and Symbian Operating System (OS) as the platform for the application to run. The encryption algorithm that implemented in the system is Advanced Encryption Standard (AES) with 128-bit block size and together with the SHA1 (Secure Hash Algorithm) hash functions. The application is designed to satisfy the user friendly interfaces and intent to be used by the end user without having the advanced knowledge in mobile security. Besides, mobile phone that able to run J2ME application is being chosen because it was designed specifically for mobile devices which support small memory footprint and low power consumption.